Electric vehicles as a transportation option for Kathmandu Valley : economics, implications on electricity planning and the environment - Dhakal, Shobhakar; Shrestha, Ram M.; Morisugi, Hisa; Bhattacharya, Sribas C.; Government of France; AIT Alumni Association (Bangkok : Asian Institute of Technology, 1996)
This study tries to find the likely implications of electric vehicles (EV s) for electricity planning and the environment in the Kathmandu Valley. Key air pollutants arising from vehicle tailpipes and batteries are addressed. Economics of an electric car from individual and social perspectives is analyzed. The study concludes that the utility planning would be affected considerably due to the change in average incremental system cost, generation schedules, capacity mix and generation mix of the hydro and thermal plants. It is found that the load management could play important role in reducing the average system cost. When all government vehicles are replaced by electric vehicles in the year 2011 , TSP, CO, HC, NOx, S02 and lead from vehicle tailpipes would be reduced by 13.8, 13.3, 6.6, 17.6, 18.9 and 15.5 percentages respectively from that of tailpipe emissions of all conventional vehicles. LPG vehicles and conventional vehicles (i.e. ICE vehicles) with strict pollutant control technologies are also found to be competitive with EV s in pollutants reduction. Under existing tax rates, electric cars are found to be competitive with those of conventional cars from the users perspective. However, this result is extremely sensitive to the uncertainties, which are large in the economic parameters. From the social perspective, the paiiial analysis conducted in this study has shown that electric cars could not compete with conventional cars. However, be due to the fact that social costs other than health impacts of air pollutants are not considered in the analysis.
Thesis (M. Eng.) - Asian Institute of Technology, 1996
A thesis submitted in partial fulfillment of the requirements for the degree of Master of engineering.
Keywords: Electric vehicles; Electricity in transportation